PENYULUHAN KESEHATAN PENYAKIT DEGENERATIF, PENYAKIT MENULAR (ISPA) DAN KEBIASAAN MENGONSUMSI MAKANAN TINGGI PURIN DENGAN KADAR ASAM URAT DI DESA KALIANGET KABUPATEN SUMENEP - Charisma, Acivrida Mega; Mulyani, Sri (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
Based on demographic conditions, the majority of residents in this village earn their living as farmers, pedicab drivers, traders, fishermen and civil servants. So that diseases arise that often occur in people, most of the diseases that disturb in this area are: gout, diabetes mellitus, and pneumonia. The research provides a comprehensive analytical review on the impact of soft drinks on human health. Consumption of soft drinks containing high amounts of sugar, not only impairs the fine control of blood sugar but also adds other complications such as overweight and obesity. The availability of calorie-dense fast food or junk food also contributes to the problem of diabetes or the emergence of type 2 obesity. Implementation method in the Community Health Development Program in East Kalianget Village, Kalianget District, Sumenep Regency, East Java Province. The methods used were counseling, distributing questionnaires and distributing leaflets. From the results of the 15 questionnaires that I have distributed, the dangers of consuming foods high in purine in gout sufferers, the side effects and long-term effects of consuming junk food, soft drinks and obesity, as many as 85% understand the counseling that has been presented. However, 15% did not understand the counseling.